Peculiarities of innate immune memory in crustaceans - Chen, Fei Low; Chou, Min Chong (Elsevier BV, 2020)
Classical characteristic of the innate immune system is the lack of ability to build up immunological memory, contrast to the adaptive immune system that is capable of “remembering” antigens, and rapidly mount a greater magnitude of immune response upon subsequent exposure to the same antigens. Peculiarly, immunological memory of innate immunity is evidenced in invertebrates. At least three different memory phenomena have been described, namely sustained unique response, recalled response, and immune shift. Studies attended to decipher the mechanistic biology of the innate immune memory reveals the role of epigenetics, which modulates the response of immune memory, and the heritability of immune memory to subsequent generations. A parthenogenetic Artemia model demonstrated successful transgenerational epigenetic inheritance of resistance trait against Vibrio campbellii. Following, the role of invertebrate hemocytes and Down syndrome cell adhesion molecule (Dscam) in innate immune memory is reviewed. While there is no vertebrate antibody homolog found in invertebrates, Dscam was found to resemble the functionality of vertebrate antibody. Insight of Dscam as immune factor was illustrated further in the current review.